Answer:
alone
Step-by-step explanation:
The answer would be -3x^2+3 x + 36
Given the equation A (x) = 30 x 8.3 ^x, we can get the
initial amount of A when x is equal to zero. Therefore:
A (0) = 30 * 8.3^0
A (0) = 30
In this case the equation grows by 8.3 times as x increases.
Therefore the growth factor is 8.3.
Answers:
initial amount = 30
growth factor = 8.3
The answers are not in the given choices. I believe you are
giving the wrong equation. If the correct equation here is:
A (x) = 680 x 4.3 ^x
Then the answers are:
initial amount = 680
growth factor = 4.3
The answers are now in the choices given.
Answer:
First equate 3x + 7 to any unknown
3x + 7 = P
Then make x the subject of the formula
3x + 7 = P
3x + 7-7= P-7
3x = P-7
3x ÷ 3 = (P-7) ÷ 3
x = (P-7) ÷3
Then interchange x with the unknown which I have as P
x = (P-7) ÷ 3
P = (x-7) ÷ 3
Then inverse of f(x)
is;
f-1(x) = (x-7) ÷ 3
Thank you.
BY GERALD GREAT.
Answer:
0.375
Step-by-step explanation:
go on google and search up "45 divided by 120" then you should have your answer lol